Intellectual property and intelligence with Learning result of educational languages of islamic Education (pai) learners in smkn 4 padang - Diones Aliaski (Jurnal Ilmiah Pendidikan Scholastic, 2018)
The purpose of this study is to know: 1) The relationship of intellectual intelligence with learning outcomes of learners in SMKN 4 Padang. 2) Relationship of emotional intelligence with learning outcomes of learners in SMKN 4 Padang. 3) The relationship of intellectual intelligence and emotional intelligence together with the learning outcomes of learners in SMKN 4 Padang. This research is a type of field research (field research). The nature of this studyis quantitative. Variables are everything that willbe the object of research observation. Population is the amount that is on the object or subject studied that includes all the characteristics or properties possessed by the object or subject it. The population in this study were students of class XI SMKN 4 Padang Year Teaching 2015/2016 which amounted to 457 people. The sample is "part of the number and characteristics possessed by the population". The sample is the partial or representative of the population under study. Data collection techniques that the authors use in this study is to use standardized test instruments. Data processing techniques used in this study is a statistical data processing techniques using correlational analysis techniques and assisted by using SPSS 20.0 for windows. Based on the results of research and discussion in Chapter IV it can be concluded as follows: 1) Proven relation Intellectual intelligence to the results of learning PAI students class XI SMKN 4 Padang because r count 0.388> r table 0.195. 2) Proven relation of emotional intelligence relate to result of learningPAI student of class XI SMKN 4 Padang because r count 0,226> r table 0,195. 3) There is proven intelligence relationship intelligence and emotional intelligence simultaneously to the results of learning PAI students class XI SMKN 4 Padang because r count 0.389> r table 0.195.